Manipulating Civic Space: Cyber Trolling in Thailand and the Philippines - Janjira Sombatpoonsiri (2018)
Abstract: In Thailand and the Philippines cyber bullies targeting internationally supported civil society groups contribute to the global trend of shrinking civic space by manipulating social media content to mobilise public disapproval of dissent. One effective tactic is to label internationally endorsed civic groups as Western agents and thereby traitors. Thailand's incumbent military regime has systematically devised methods to suppress dissent, while the Philippines' illiberally inclined government has diminished civic space. Social media is a crucial tool for both governments to quell critics. "Cyber troops" are organised by the Thai state and even private traditionalist citizens. In the Philippines, "keyboard armies" tend to be President Duterte's supporters and are in some cases allegedly paid. These actors promulgate pro-government messages, surveil and report civic defiance to the authorities, bully and threaten critics online, and orchestrate offline harassment campaigns. Cyber tr